Comparative Study on the Development of Latent Fingerprints Using Soot Deposition and Black Fingerprint Powder (International Journal of Scientific Research in Science and Technology, 2025)
The study aids in how effectively black fingerprint powder and soot deposition work to form prints to produces superior ridge clarity and detail a common method is fingerprint powder, but soot deposition is frequently cheap and may use easily accessible materials. Soot deposition might not have as much thorough scientific backing as commercial powders. A methodical investigation offers a scientific foundation for its effectiveness, The present study was conducted to identify which gave well-defined print among these two methods, as a natural byproduct, soot may be less damaging to the environment than some of the synthetic ingredients used in fingerprint powders. Measure the cost efficiency between the soot deposition method and the powdered method. The first approach uses black powder to create fingerprints on a glass surface, whereas the second method uses fire-derived soot. These two techniques have been used to gather and produce a total of 100 samples.